New Technologies, Development and Application VII Advanced Production Processes and Intelligent Sytems, Volume 1 - Karabegovic, Isak; Kovačević, Ahmed; Mandzuka, Sadko (Lecture Notes in Networks and Systems, 2024)
XVI, 767 p. 444 illus., 360 illus. in color.